2018
DOI: 10.1016/j.ygeno.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of Odontobutis haifengensis (Perciformes, Odontobutiae): A unique rearrangement of tRNAs and additional non-coding regions identified in the genus Odontobutis

Abstract: Herein, the complete mitochondrial genome of Odontobutis haifengensis was sequenced for the first time. The O. haifengensis mitogenome was 17,016bp in length and included 13 protein-coding genes, 22 transfer RNAs (tRNAs), 2 ribosomal RNAs (rRNAs), and a control region (CR). The genome organization, base composition, codon usage, and gene rearrangement was similar to other Odontobutis species. Furthermore, a tRNA gene rearrangement within the SLH cluster was found to be identical to other Odontobutis species. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The result was consistent with previous studies that the fungal group I introns appears to result from numerous losses and gains of the mobile genetic elements 40,43,66,67 . The arrangement of mitochondrial genes can also serve as an important reference for revealing phylogenetic relationships among species [68][69][70] . In this study, we found that the arrangement of mitochondrial genes was highly variable in Polyporales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result was consistent with previous studies that the fungal group I introns appears to result from numerous losses and gains of the mobile genetic elements 40,43,66,67 . The arrangement of mitochondrial genes can also serve as an important reference for revealing phylogenetic relationships among species [68][69][70] . In this study, we found that the arrangement of mitochondrial genes was highly variable in Polyporales.…”
Section: Discussionmentioning
confidence: 99%
“…The arrangement of mitochondrial genes can also serve as an important reference for revealing phylogenetic relationships among species 68 70 . In this study, we found that the arrangement of mitochondrial genes was highly variable in Polyporales .…”
Section: Discussionmentioning
confidence: 99%
“…The first step was to obtain the sequences of the 16S rRNA, COI and Cyt b genes by PCR with universal primers [ 5 , 22 , 23 ], and the sequence gaps in these mitochondrial genes can then be obtained by the specific primers designed based on the known sequences listed above; the resulting fragments of the PCR products, obtained with only seven sets of PCR primers, are shorter than 3000 bp and can be sequenced by Sanger sequencing. Compared to other sequencing methods, such as PCR amplification with multiple PCR primer pairs (> 15) [ 21 , 24 ] and next-generation sequencing [ 13 , 19 ], our strategy can avoid nonspecific amplification or other problems resulting from sequence assembly.…”
Section: Discussionmentioning
confidence: 99%
“…To test the utility of selected markers for studies at the species level, we reconstructed a species tree of four species of freshwater sleepers ( Odontobutis , Gobiiformes), whose relationships are unresolved (Ren & Zhang, ; Zhong et al, ). The species tree was reconstructed based on exon capture data of the chosen markers, including five individuals of each species of Odontobutis sinensis , O. potamophila, and O. yaluensis and one individual of O. haifengensis .…”
Section: Methodsmentioning
confidence: 99%
“…To test the utility of selected markers for studies at the species level, we reconstructed a species tree of four species of freshwater sleepers (Odontobutis, Gobiiformes), whose relationships are unresolved (Ren & Zhang, 2007;Zhong et al, 2017). ASTRAL v4.11.1 (Mirarab & Warnow, 2015) was used to infer the species tree.…”
Section: Testing Phylogenetic Usefulness Of the Markers Selected Anmentioning
confidence: 99%